Experimental infection with Leishmania chagasi in immunosuppressed Balb/c mice: cytokines and parasite burdens - Hoffmann,JL (2009)
The immune response in leishmaniasis may result in a polarization of the T lymphocyte subpopulation, altering cell phenotype and resulting in immune protection or disease exacerbation. Leishmania may persist in the body either during asymptomatic infections or after treatment, which represents high risk under immunosuppression. The objective of this study was to evaluate the effect of infection with immunosuppression by dexamethasone associated with pentoxifylline on animal weight, spleen weight, spleen and hepatic parasitic load and immunopathology, as well as the IFN-γ and IL-10 production in spleen cell culture of Balb/c mice infected with Leishmania chagasi. The infection did not cause body weight gain in animals, but both the weight and size of the spleen were increased. The immunosuppression using dexamethasone associated with pentoxifylline affected body weight gain and spleen weight and size in both infected and non-infected animals. The immunosuppression did not significantly alter the course of the splenic or hepatic parasite burden. Dexamethasone and pentoxifylline significantly affected cytokine production, but did not influence the Th1/Th2 ratio in infected animals.